A study of smart charging for electric vehicles using constant-current and constant-voltage technology - Tole Sutikno; Tri Wahono; Ardiansyah Ardiansyah (Institute of Advanced Engineering and Science, 2024)
The role of electric vehicles (EVs) is very important in the coming years because of their environmental friendliness and ability to absorb excess electricity from renewable energy sources (RES). Charging EVs will have an immediate negative impact on the power grid. EV smart charging provides a solution to these problems. For sustainable energy management, smart charging technology offers significant advantages in terms of faster charging times and optimized grid usage. By leveraging advanced algorithms and real-time communication capabilities, smart chargers enhance the efficiency, convenience, and environmental sustainability of EV charging infrastructure. Constant-current (CC) and constant-voltage (CV) technologies are essential components of smart charging systems, contributing to improved charging efficiency, battery safety, and grid stability. By regulating the charging process and optimizing power flow, these technologies play a crucial role in advancing the adoption of EVs and promoting sustainable energy management. When advanced CC-CV technologies are added to smart charging systems, the whole paradigm changes. Charging efficiency goes up by 40%, charging time goes down by 50%, and the grid's impact is reduced by 50% through better energy distribution.